2011
DOI: 10.7851/ksrp.2011.17.3.001
|View full text |Cite
|
Sign up to set email alerts
|

Classification of rural villages based on Landscape Indices - Focusing on Landscape Ecological Aspects -

Abstract: : This study aims to analyse the landscape ecological characteristics of 39 rural villages in Korea and classify them according to their characteristics. After producing a land-use map of rural villages, this study quantified the landscape ecological characteristics of the subject sites as 18 landscape indexes using Fragstats. By applying the landscape index as a variable, selecting 4 factor through principal component analysis and conducting a cluster analysis, it classified them into 3 groups. Rural villages… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Park et al developed questionnaires to study people's emotions towards Hanok, a traditional Korean building, based on the materials and forms of the roof and the overall shape of the building [13]. Kim suggested that rural landscapes should be managed visually, and pointed out that the use, number of floors, and structure of buildings, as well as their roof types, materials, and colors, may reflect rural architectural characteristics [14].…”
Section: Research On the Elements Of Architectural Featuresmentioning
confidence: 99%
See 2 more Smart Citations
“…Park et al developed questionnaires to study people's emotions towards Hanok, a traditional Korean building, based on the materials and forms of the roof and the overall shape of the building [13]. Kim suggested that rural landscapes should be managed visually, and pointed out that the use, number of floors, and structure of buildings, as well as their roof types, materials, and colors, may reflect rural architectural characteristics [14].…”
Section: Research On the Elements Of Architectural Featuresmentioning
confidence: 99%
“…Studying these places is of great significance for understanding changes in village architectural features at the street level. Additionally, as the fifth facade of traditional Chinese architecture, roofs at the building level have a significant impact on a building's features [10,11,14]. However, at present, numerous studies have only analyzed roof form or roof color, neglecting to holistically assess roof form, material, and color.…”
Section: Summary Of Previous Studies and The Framework Of This Studymentioning
confidence: 99%
See 1 more Smart Citation